2012
DOI: 10.1016/j.entcom.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The MINWii project: Renarcissization of patients suffering from Alzheimer’s disease through video game-based music therapy

Abstract: Abstract. MINWii, a new serious video game targeting Alzheimer and demented patients, is a simple Music Therapy tool usable by untrained care givers. Its objective is to improve patients' self-image (renarcissization) to reduce behavioral symptoms, which are an important cause of institutionalization. With MINWii, elderly gamers use Wiimotes to improvise or play predefined songs on a virtual keyboard. We detail our design process, which addresses the specific features of dementia: this iterative refinement sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(106 citation statements)
references
References 22 publications
1
103
0
2
Order By: Relevance
“…Since the publication of our previous recommendations on the use of SG (Robert et al, 2014), a number of SG were developed and tested with older people with MCI and dementia to train physical and cognitive abilities and to improve emotional wellbeing (Beneviste et al, 2012; Manera et al, 2015; Ben-Sadoun et al, 2016). These studies showed promising results, but also a number of usability challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the publication of our previous recommendations on the use of SG (Robert et al, 2014), a number of SG were developed and tested with older people with MCI and dementia to train physical and cognitive abilities and to improve emotional wellbeing (Beneviste et al, 2012; Manera et al, 2015; Ben-Sadoun et al, 2016). These studies showed promising results, but also a number of usability challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we systematically analyzed the Strengths, Weaknesses, Opportunities and Threats (SWOT) of employing SG with these patients, and reported practical guidelines on when, where, and with whom SG should be employed, and to specify which categories of patients and which abilities should be targeted. Since then, a few empirical studies were published on the use of SG in these populations, describing the feasibility of employing SG targeting improvements in social/emotional wellbeing (Beneviste et al, 2012), SG training cognitive abilities such as executive functions (Manera et al, 2015), and Serious Exergames including a combination of cognitive training and physical training (Ben-Sadoun et al, 2016). A few more SG were designed for these patients to train cognitive abilities such as memory (Kim et al, 2015) and several aspects of visual attention (Mader et al, 2012), but they have not been tested so far on people with ND.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benveniste et al [10] suggested using video game based music therapy to improve patients' self-image to reduce behavioral symptoms. Makedon et al [11] proposed ZPLAY, a game based, web-based user interface system which is designed to provide intervention therapy for AD patients.…”
Section: Results Smentioning
confidence: 99%
“…Dans cette optique, la faisabilité (c.-à-d., critères d'ergonomie, critères d'engagement, critères d'utilisation) et les effets d'entraînement sur les paramètres psychologiques, comportementaux et physiologiques restent à étudier. En effet, bien qu'une étude récente ait montré que l'utilisation des serious games était possible et influençait positivement le comportement de patients atteints sévèrement de la MA [70], il n'existe aujourd'hui aucun serious game conceptualisé autour de l'EE et de l'APRA d'intensité élevée dédié au patient Alzheimer.…”
Section: Conclusion Et Perspectivesunclassified